Iklim Organisasi dan Komitmen Kerja Karyawan Puskesmas - Tri Yaumil Alfa; Dwi Iramadhani; Azwar Djafar (Jurnal Psikologi Terapan, 2020)
The working atmosphere in the company is very important in determining employee performance and work commitment. This study aims to determine the relationship of organizational climate with work commitments for employees in Puskesmas Kutamakmur, Aceh Utara. The hypothesis being tested is a positive relationship between organizational climate and work commitments for employees who work in Puskesmas Kutamakmur. The sampling technique used in this study was sampling saturation with data collection methods through the organizational climate scale and Likert work commitment scale model for 120 employees. The reliability test produces an organizational climate of 0.880 and a work commitment of 0.911. Hypothesis test results show a positive relationship with organizational climate and work commitment based on the value of the correlation coefficient r = 0.455 (p = 0,000).